Knowledge Management: Leveraging Competitive Advantage & Organizational Competence – A Study of Indian Organisations in General - Shradha Nain (Universitas Gunadarma, 2011)
Today the concept of knowledge management is studied as a “competitive advantage of the firm”and human resource as “knowledge capital”. Knowledge Management (KM) has made its entryin both public and private sectors of India. There has been advent of information technology inthe last decade and the emergence of knowledge worker and the knowledge economy. There isfocus on effectiveness of the organization through internal collaborations and process ofknowledge Management and knowledge management systems. Information and communicationtechnologies and human capital congruence is playing an important part in leveragingknowledge for individual’s personal growth and organizations competitive advantage whichhelps in economic development. The paper aims to review the latest knowledge managementdevelopments and practices of KMS.